2010
DOI: 10.1007/s10549-010-0915-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of primary breast sarcoma

Abstract: Primary sarcoma of the breast is an extremely rare and heterogeneous disease. The rarity of this tumour limits most studies to small retrospective case reviews and case reports and has made clinicopathological study difficult. This article reviews the current literature on the diagnosis and management of breast sarcoma. The optimal treatment of breast sarcoma involves a multidisciplinary team prior to the initiation of treatment. Patients with tumours less than 5 cm that are easily resectable should undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 49 publications
4
91
1
8
Order By: Relevance
“…C. Adem et al have quoted an incidence of 0.0006% [4]. Sammy Al-Benna reviewed English literature and found that 98.5% of breast sarcoma occurred in women and 1.5% in men [5].…”
Section: Discussionmentioning
confidence: 99%
“…C. Adem et al have quoted an incidence of 0.0006% [4]. Sammy Al-Benna reviewed English literature and found that 98.5% of breast sarcoma occurred in women and 1.5% in men [5].…”
Section: Discussionmentioning
confidence: 99%
“…За даними Al-Benna at al. (2010), захворюваність становить 44,8 на 10 млн жінок [2]. СГЗ характеризуються частими рецидивами, ранньою появою віддалених гематогенних метастазів і несприятливим прогнозом.…”
Section: вступunclassified
“…31 Majority of studies did not find any benefit for adjuvant radiotherapy. 1,7,11,32 But McGowan et al and Johnstone et al demonstrated significant benefits for patients.…”
Section: Radiotherapymentioning
confidence: 99%